Prince2 Methodology: An Innovative Way for Improving Performance of Malaysian Automotive Industry - Saima, Said; Abdullah, Ibrahim; Omme, Asma; Muhammad Saad, Khan; Junaid, Akhter (Universiti Teknikal Malaysia Melaka, 2013)
The role of project management is identically essential for organizations and it’s converted into an important issue for implementing modern projects. Operations & Management division is the spine of any corporate organization,and it is the key factor for progress the performance of the industry. International competition in automotive industry compulsory required, well-organized project management in each area, for satisfaction of clients and quality. The novel approach of Project Management is Project Management PRINCE2 (PMP2), which is the generic framework, which design to suit every type of project in industry. Therefore, the aim of this research is to investigate the impact of project management prince2 methodology in Malaysian automotive industry. PRINCE2 is a structured method for effective project management. PRINCE2 has strongly established in UK and spread all over the world fluently; as a generic, process based approach of project management. In view of the fact that its emphasis on, the dividing the project into manageable and controllable stages. This research will encourage the implementation of Prince2 methodology in automotive industry of Malaysia. Additionally, it will encourage the prospect applications of PRINCE2, which ultimately improve the human performance in automotive industry.